STRATEGY FOR HANDLING CHILDREN VICTIMS OF SEXUAL VIOLENCE BY DP5A CITY OF SURABAYA - Irfan Dwi Saputra; Tukiman - Tukiman (DIA: Jurnal Administrasi Publik, 2021)
Cases of sexual violence against children are currently still in the spotlight. Many factors cause this to happen, such as the social environment, advances in information and communication technology, and opportunities. Children who are victims of sexual violence will experience physical, psychological and psychological suffering, as well as social suffering.In dealing with child victims of sexual violence, DP5A has a strategy for children who are victims of sexual violence, namely collaborating with institutions related to handling, picking up the ball with the Puspaga, and being the manager of PPTP2A. The program of the strategy is to provide social rehabilitation, legal assistance, and health identification. This research uses descriptive qualitative method, using SWOT analysis technique. This research results that the strategy for handling child victims of sexual violence by DP5A has been running by utilizing strengths and opportunities, but it is still not optimal enough due to weaknesses and threats in handling.